An Estimated DSGE Model of Austria, the Euro Area and the U.S.: Some Welfare Implications of EMU - Fritz Breuss; Jorge A. Fornero (FIW - Research Centre International Economics, 2009)
We build a fully micro-founded dynamic general equilibrium (DSGE) model, which is estimated employing Bayesian methods. The model captures the most salient features of Austria as a small open economy, the Euro Area (EA) and the United States (U.S.). Further analysis is conducted through numerical simulations to examine how nominal and real shocks are propagated. Besides, welfare costs of nominal rigidities are calculated. We distinguish two sample periods, pre-EMU' and EMU'. In the former, we maintain the assumption of full commitment of respective (independent) Central Banks towards their monetary rules, whereas in the latter, the monetary policy of Austria is fully aligned with the European Central Bank. Main results are derived from Bayesian estimation and simulation of the estimated model. Welfare calculations from the estimated model suggest that in the pre-EMU period, the EA and Austria present welfare costs close to one percent of steady-state consumption, whereas the U.S. welfare costs is slightly higher (-1.52 percent). As it would be expected, in the second subsample, welfare costs in the EA decrease, indicating an improvement in the allocation during the EMU regime (similarly in the U.S.), whereas in Austria welfare costs go up.
Keywords: E42; F41; F42; 330; Monetary Policy; NOEM; DSGE models; Austria; EURO area; U.S.